Online Learning Evaluation of Drug Information Service Lectures in The Faculty of Pharmacy, Sanata Dharma University - Christasani, Putu Dyana; Wijoyo, Yosef (Media Farmasi: Jurnal Ilmu Farmasi, 2023)
The COVID-19 pandemic impacted the need for new adaptations in the learning process, namely by implementing an online learning system. This method remains a trend in the future, so it is necessary to conduct research to evaluate the online lectures. The evaluation process evaluates at the microlevel, namely the process, learning outcomes, and student perceptions of the Drug Information Services course.This research is evaluative and descriptive, with a cross-sectional design and quantitative and qualitative approaches. Research was conducted at the Faculty of Pharmacy, Sanata Dharma University. The respondents were 124 USD Pharmacy S-1 students who took the Drug Information Services course in the odd semester of 2020–2021. Student learning outcomes and perceptions were obtained using validated assessment rubrics and reflection questionnaires.The results showed that the implementation of Drug Information Services lectures went according to the semester learning plan; there were minor revisions to improve the dynamics of student discussions. Students learning outcomes are in the "very good" category, except for the OSCE examination, which is relatively sufficient. Student have a positive perception of this online lecture. In conclusion, this online lecture can be maintained for the future with a slight modification to the oral exam, which uses the offline method by implementing strict health protocols.